An In vitro Study of Bio-Control and Plant Growth Promotion Potential of Salicaceae Endophytes - Shyam L. Kandel; Andrea Firrincieli; Pierre M. Joubert; Patricia A. Okubara; Natalie D. Leston; Kendra M. McGeorge; Giuseppe S. Mugnozza; Antoine Harfouche; Soo-Hyung Kim; Sharon L. Doty (Frontiers in Microbiology, 2017)
Microbial communities in the endosphere of Salicaceae plants, poplar (Populus trichocarpa) and willow (Salix sitchensis), have been demonstrated to be important for plant growth promotion, protection from biotic and abiotic stresses, and degradation of toxic compounds. Our study aimed to investigate bio-control activities of Salicaceae endophytes against various soil borne plant pathogens including Rhizoctonia solani AG-8, Fusarium culmorum, Gaeumannomyces graminis var. tritici, and Pythium ultimum. Additionally, different plant growth promoting traits such as biological nitrogen fixation (BNF), indole-3-acetic acid (IAA) biosynthesis, phosphate solubilization, and siderophore production were assessed in all bio-control positive strains. Burkholderia, Rahnella, Pseudomonas, and Curtobacterium were major endophyte genera that showed bio-control activities in the in-vitro assays. The bio-control activities of Burkholderia strains were stronger across all tested plant pathogens as compared to other stains. Genomes of sequenced Burkholderia strains WP40 and WP42 were surveyed to identify the putative genes involved in the bio-control activities. The ocf and hcnABC gene clusters responsible for biosynthesis of the anti-fungal metabolites, occidiofungin and hydrogen cyanide, are present in the genomes of WP40 and WP42. Nearly all endophyte strains showing the bio-control activities produced IAA, solubilized tricalcium phosphate, and synthesized siderophores in the culture medium. Moreover, some strains reduced acetylene into ethylene in the acetylene reduction assay, a common assay used for BNF. Salicaceae endophytes could be useful for bio-control of various plant pathogens, and plant growth promotion possibly through the mechanisms of BNF, IAA production, and nutrient acquisition.